Revisiting the role of standardization and patenting of scintillation engineering in innovation processes - Danylenko, Yu.; Lyubynskiy, V.; Pavlova, An. (Functional Materials, 2018)
The analysis of studies on standardization and patenting for scintillation engineering of innovation processes is carried out and a model of their interaction is developed.